Polymer of intrinsic microporosity (PIM-1) enhances hydrogen peroxide production at Gii-Sens graphene foam electrodes - Azevedo Beluomini, Maisa [UNESP]; Wang, Yu; Wang, Lina; Carta, Mariolino; McKeown, Neil B.; Wikeley, Simon M.; James, Tony D.; Lozano-Sanchez, Pablo; Caffio, Marco; Ramos Stradiotto, Nelson [UNESP]; Valnice Boldrin Zanoni, Maria [UNESP]; Marken, Frank (Elsevier, 2022)
3D-graphene foam electrodes (Gii-Sens) immersed in a phosphate buffer solution of pH 7 are shown to generate hydrogen peroxide at a significantly faster rate in the presence of a nanoparticulate polymer of intrinsic microporosity (PIM-1). The effect is demonstrated to be associated at least in part with oxygen binding into PIM-1 under triphasic conditions. The release of the oxygen at the electrode|solution interface quadruples H2O2 production. Generator–collector experiments are performed with a graphene foam disk generator and a platinum disk electrode collector to allow in situ detection of hydrogen peroxide and oxygen.
Keywords: Catalysis; Disinfection; Generator–collector voltammetry; Graphene; Hydrogen peroxide